Constructing Meaning and Enhancing Well-Being: The Role of Place Attachment, Place Identity, and Sense of Place in Architectural Studio Environments - Emma S. EKPO; Mokọ́ládé JOHNSON (FUDMA Journal of Engineering and Technology, 2025)
The architectural studio environment represents a distinctive educational setting that transcends its physical confines. Beyond the physical structures are also the social relationships, activities, and attitudes of the users that are significant to the learning environment. Despite its pedagogical centrality, limited empirical research has explored how students in African institutions, especially in Nigeria, experience and attach meaning to their studio environments. Consequently, this study aims to bridge that gap by examining how the concepts of place attachment, place identity, and sense of place are used to describe the quality of students’ relationships with the architectural studio environments in three federal universities Southwest Nigeria, Obafemi Awolowo University (OAU), University of Lagos (UNILAG), and Federal University of Technology Akure (FUTA). Drawing on interdisciplinary perspectives from environmental psychology, educational theory, and architectural pedagogy, the research explores how students internalize the studio as a place and how these interactions influence students’ sense of belonging, learning experiences and well-being. Place is a dimension shaped by people’s relationship with physical environments, individual and group activities, and meaning. Employing qualitative methods, including in-depth interviews, participant observation, and spatial analysis, the study reveals that a strong emotional connection to the studio fosters deeper engagement and identity formation among architecture students. The findings highlight the pivotal role of spatial design and social dynamics in shaping the meanings and educational experiences of students and tutors, suggesting that intentionally designed studio environments and culture can have a positive impact on students’ sense of place, promote learning outcomes and contribute to overall well-being.